2014
DOI: 10.1186/1478-811x-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Graded inhibition of oncogenic Ras-signaling by multivalent Ras-binding domains

Abstract: BackgroundRas is a membrane-associated small G-protein that funnels growth and differentiation signals into downstream signal transduction pathways by cycling between an inactive, GDP-bound and an active, GTP-bound state. Aberrant Ras activity as a result of oncogenic mutations causes de novo cell transformation and promotes tumor growth and progression.ResultsHere, we describe a novel strategy to block deregulated Ras activity by means of oligomerized cognate protein modules derived from the Ras-binding domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…To quantify cell invasion, we measure wound confluence using a modified scratch wound invasion assay where cells are overlaid with a ~1.5 mm-thick layer of Matrigel, a protein mixture that recapitulates the ECM (Fig 1B); this setup requires cells to invade through a 3D matrix 30,31 . Our results show that there is variability in how quickly pancreatic ductal cells move into the wound gap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify cell invasion, we measure wound confluence using a modified scratch wound invasion assay where cells are overlaid with a ~1.5 mm-thick layer of Matrigel, a protein mixture that recapitulates the ECM (Fig 1B); this setup requires cells to invade through a 3D matrix 30,31 . Our results show that there is variability in how quickly pancreatic ductal cells move into the wound gap.…”
Section: Resultsmentioning
confidence: 99%
“…To measure cell invasion through a 3D matrix, we perform modified scratch wound invasion assays with an overlay of Matrigel to simulate the ECM 30,31,84 . We plate cells in the wells of a 96-well plate with a thin Matrigel (100 μg/ml) layer for cell attachment at 95% confluency, create a scratch wound, overlay the scratch with a ~1.5 mm-thick layer of 8 mg/ml Matrigel (Corning), and perform time-lapse imaging using the IncuCyte Zoom (Essen Bioscience) at 5% CO 2 and 37°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…While a subset of these miRNAs are overexpressed in cancers and shown to target tumor suppressor genes, hence termed oncogenic miRNAs or oncomiRs, some other miRNAs that target oncogenes are underexpressed in cancers, which are often called tumor-suppressor-like miRNAs. Certain miRNAs are known to have a dual role, either oncogenic or tumor-suppressive, depending on the cancer-specific context [22] .…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies has categorically shown that oncogenic Ras triggers cell cycle entry and DNA synthesis independently of growth factors [1,2]. Accordingly, inhibition of native Ras by a variety of approaches including microinjection of inhibitory Abs [3], dominant negative RasS17N [4], expression of Ras-GTP scavenging modules [5], small-molecular allosteric inhibitors of Ras function [6] or by preventing upstream steps in Ras activation [7] inhibits DNA synthesis and cell proliferation. More recently, the analysis of engineered MEF lines devoid of all 3 Ras genes (termed Rasless) has underscored the indispensable nature of Ras in cell cycle progression, as cells rendered Rasless were forced into a quiescencelike state and ceased to proliferate [8,9].…”
mentioning
confidence: 99%